L’agriculture de conservation à la croisée des chemins en Afrique et à Madagascar - Georges Serpantié (VertigO)
Conservation agriculture (CA) represents farming systems obeying three principles : minimal mechanical soil disturbance, permanent organic cover, and diversified crops. On the basis of its effects on soil ecology, carbon sequestration, work productivity and massive adoption in some agricultures over the world, it was presented by its promoters as the only sustainable and appropriate system for all the contexts, and consequently universally diffused in the name of the sustainable development. By field surveys and documentation analysis, our research focused on the history of CA extension on worldwide scale. We emphasized the very specific origin of CA and disparity of its adoption between regions and types of exploitations. Then the possible causes of the apparent resistance of African and Malagasy agricultures were analysed : constraints related to the semi-aridity and the agro-pastoral civilisations, rival solutions, still unsuited technical sequences, and importance of the time et diversity factors in the innovation process. In spite of this multiple causality, the postulate of universality of CA brings back the question of the adoption to the only political and financial management of diffusion. It is however necessary to prove its transferability towards any context, and its ecological sustainability. We recommend the pursuance of the effort of improvement by analyzing the context of the farming systems and basing the research on the practices, the local knowledge and the innovation capacity of farmers and communities, and to follow other tracks in parallel.